Rationalizing Korea : the rise of the modern state, 1894-1945 - Hwang, Kyung Moon (University of California Press, 2016)
"The first book to explore the institutional, ideological, and conceptual development of the modern state on the peninsula, Rationalizing Korea analyzes the state's relationship to five social sectors, each through a distinctive interpretive theme: economy (developmentalism), religion (secularization), education (public schooling), population (registration), and public health (disease control). Kyung Moon Hwang argues that while this formative process resulted in a more commanding and systematic state, it was also highly fragmented, socially embedded, and driven by competing, often conflicting rationalizations, including those of Confucian statecraft and legitimation. Such outcomes reflected the acute experience of imperialism, nationalism, colonialism, and other sweeping forces of the era"--Provided by publisher.